Travels and Cities of The Ḥadith Studies: An Analysis of Buldan in the Islamic Intellectual History - Muhammad Fawwaz Bin Muhammad Yusof (Brill, 2024)
Al-Bayan: Journal of Qur'an and Hadith Studies Volume 21: Issue 3 (page: 315–334) This is a preprint article, it offers immediate access but has not been peer reviewed.